Impostor phenomenon and its association with perceived stress and anxiety among students in medical and social sciences at a Swedish university - Jansson, Anna; Boman, Jens; Schéle, Ingrid; Holmström, Stefan; Rozental, Alexander; Semb, Olof; Fahlström, Martin; Stenman, Laura; Bitar, Aziz; Lindquist, David (Frontiers in Medicine, 2025)
IntroductionPsychological distress is of concern among university students worldwide, more so than in a comparable working population. The impostor phenomenon (IP) describes feelings of inadequacy often experienced by individuals struggling to internalize success despite evidence to the contrary. IP is prevalent among university students and has been identified as a significant factor in understanding psychological distress within this population. This study aimed to investigate the prevalence of IP and its association with perceived stress and anxiety in dental, law, medical, nursing and psychology university students.MethodsA web-survey consisting of the Clance Impostor Phenomenon Scale (CIPS), the Perceived Stress Scale-4 (PSS-4), the Generalized Anxiety Disorder-2 (GAD-2), and sociodemographic questions were completed by 968 university students registered at a Swedish university during 2022 and 2023. The prevalence of IP, perceived stress, and anxiety was calculated. Pearson’s correlation coefficient and multiple linear regression were used to examine the relationship between the variables.Results64.0% of the participants scored above the cut off value for experiencing IP (CIPS score ≥62). According to cut-off levels developed to categorize the intensity of IP experiences 8.4% of participants had low experiences of IP, 26.0% moderate, 42.6% frequent, and 23.0% intense experiences of IP. Of all participants, 91.6% had at least moderate experiences of IP and 65.6% had frequent to intense experiences of IP. Women scored significantly higher on CIPS than men. In contrast, neither attending semester nor age group significantly impacted CIPS scores. Finally, there was a moderate correlation between the levels of perceived stress and anxiety, respectively, and the IP scores.ConclusionThis study suggests that the majority of dental, medical, nursing, psychology and law students experience severe IP. Moreover, this study provides valuable insights into the association of IP with perceived stress and anxiety. The results underscore the significance of exploring IP and its link to psychological distress, suggesting that interventions aimed at diminishing IP may play a crucial role in enhancing the well-being of university students.